2022
DOI: 10.1002/tafs.10345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Native Fish Passage through Brandon Road Lock and Dam, Des Plaines River, Illinois, Using Fin Ray Microchemistry

Abstract: This study examined evidence of native fish passage through Brandon Road Lock and Dam (BRLD) on the Des Plaines River, Illinois, in light of proposed modifications to prevent the upstream passage of invasive carps. Direct evidence of upstream passage by native fishes at BRLD is lacking and could help to inform assessment of the impacts of barrier technology installation. Fin ray microchemistry was used to assess upstream BRLD passage in the native taxa Centrarchidae, Catostomidae, Ictaluridae, and Lepisosteida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Specifically, Linfield (1985) noted persistence of the larger‐fish‐upstream pattern despite semipermeable (i.e., passible only during portions of the year) weirs fragmenting the river. Lock‐and‐dam structures such as those on the Ohio River are not absolute barriers to fishes that produce drifting offspring (e.g., Smith and Hightower 2012; Snyder et al 2022; La Hood et al 2023), and this might explain the persistence or colonization of Silver Chub among shorter stream fragments in the Ohio River. We found that catch of age‐0 Silver Chub increased consistently as fragment size increased from 11 to 183 km, and there was a consistent decline in the proportion of years in which age‐0 individuals were collected as fragment length declined below 100 km.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Linfield (1985) noted persistence of the larger‐fish‐upstream pattern despite semipermeable (i.e., passible only during portions of the year) weirs fragmenting the river. Lock‐and‐dam structures such as those on the Ohio River are not absolute barriers to fishes that produce drifting offspring (e.g., Smith and Hightower 2012; Snyder et al 2022; La Hood et al 2023), and this might explain the persistence or colonization of Silver Chub among shorter stream fragments in the Ohio River. We found that catch of age‐0 Silver Chub increased consistently as fragment size increased from 11 to 183 km, and there was a consistent decline in the proportion of years in which age‐0 individuals were collected as fragment length declined below 100 km.…”
Section: Discussionmentioning
confidence: 99%
“…Understudied species such as small-bodied fishes are functionally important within riverine systems due to their high abundance (Ickes et al, 2022) and provisioning of multiple ecological functions including prey resources and nutrient cycling (Holmlund & Hammer, 1999). Furthermore, the focus of most prior environmental history research has been at relatively small spatial extents such as one reach (Crook & Gillanders, 2006;Daugherty et al, 2019;Laughlin et al, 2016;Rude & Whitledge, 2019;Snyder et al, 2022;Zeigler & Whitledge, 2010), with some more recent work conducted in large rivers such as the Amazon (Cañas & Pine III, 2011;Hermann et al, 2016;Pouilly et al, 2014). Whereas smallscale studies can predict local factors affecting habitat use, largescale studies quantify general patterns across a system that support river-wide processes (Miranda et al, 2008(Miranda et al, , 2020) that can inform inter-jurisdictional management and conservation actions.…”
Section: Introductionmentioning
confidence: 99%